The Relationship Between Particle Injection Rate Observed at Geosynchronous Orbit and Dst Index during Geomagnetic Storms - Ga-Hee Moon; Byung-Ho Ahn (Journal of Astronomy and Space Sciences, 2003)
To examine the causal relationship between geomagnetic storm and substorm, we investigate the correlation between dispersionless particle injection rate of proton flux observed from geosynchronous satellites, which is known to be a typical indicator of the substorm expansion activity, and Dst index during magnetic storms. We utilize geomagnetic storms occurred during the period of 1996˜2000 and categorize them into three classes in terms of the minimum value of the Dst index (Dstmin); intense (--200 nT ≤ Dstmin≤ -100 nT), moderate (--100 nT ≤ Dstmin≤ -50 nT), and small (--50 nT ≤ Dstmin≤ -30 nT) storms. We use the proton flux of the energy range from 50 keV to 670 keV, the major constituents of the ring current particles, observed from the LANL geosynchronous satellites located within the local time sector from 18:00 MLT to 04:00 MLT. We also examine the flux ratio (fmax/fave) to estimate particle energy injection rate into the inner magnetosphere, with fave and fmax being the flux levels during quiet and onset levels, respectively. The total energy injection rate into the inner magnetosphere can not be estimated from particle measurements by one or two satellites. However, the total energy injection rate should be at least proportional to the flux ratio and the injection frequency. Thus we propose a quantity, ``total energy injection parameter (TEIP)", defined by the product of the flux ratio and the injection frequency as an indicator of the injected energy into the inner magnetosphere. To investigate the phase dependence of the substorm contribution to the development of magnetic storm, we examine the correlations during the two intervals, main and recovery phase of storm separately. Several interesting tendencies are noted particularly during the main phase of storm. First, the average particle injection frequency tends to increase with the storm size with the correlation coefficient being 0.83. Second, the flux ratio (fmax/fave)